Sun of the children: ludonarrativity in abstract character-driven game design - Vang, Hue (University of Wisconsin--Stout, 2018)
Sun of the Children is a 2D digital game that focuses on the issue of ludonarrative dissonance, a term coined by Clint Hocking that describes the disconnect between gameplay and story. This dissonance is present because of the use of cinematic cutscenes: verbal and written narration that are borrowed from film and literature to fill in the gaps of digital game storytelling that gameplay cannot clearly execute. By creating a new narrative model using ludonarrative mechanics, this exploratory creative thesis will implement and analyze devices such as detailed character animation states, responsive environments and qualitative game mechanics that arc in parallel with character development. By rejecting the use of cinematic cutscenes, verbal and/or textual storytelling, this project will further digital games' evolution toward integrated narrative experiences.
Keywords: Video games; Digital storytelling; Play